The Effect of Honey Fermentation on the Cell Appearance in the Seminiferous Tubule Wall of Rats Induced by Cisplatin - Ulviena, Lulu; Hadi, Restu Syamsul (Junior Medical Journal, 2023)
Background: Cisplatin is the most effective cancer treatment used in chemotherapy. Cisplatin works by inducing oxidative stress, but it also has toxic side effects on healthy cells in the male reproductive organs. Therefore, there is a need for a solution to reduce the side effects of cisplatin. Honey fermentation is a natural substance that can reduce the toxicity of cisplatin. Honey is known as “The food of God” which is a gift of sustenance from Allah SWT due to its extraordinary benefits. Methodology: This study utilized primary data with an experimental posttest-only control group design conducted in vivo. The research involved four experimental groups of rats: a control group without any treatment, a cisplatin group, a 5% honey fermentation group exposed to cisplatin, and a 10% honey fermentation group exposed to cisplatin. All rats were weighed before, during, and after the treatment. Subsequently, HE staining was performed for both descriptive and quantitative observations. Results: Honey fermentation can provide a protective effect on primary spermatocytes and Leydig interstitial cells, almost reaching normal levels. The highest improvement was observed in the 5% honey fermentation group for primary spermatocytes and the 10% group for Leydig interstitial cells. Conclusion: Honey fermentation administration can be protective for testicular organ cells against the side effects of cisplatin. From an Islamic perspective, Allah has created honey for consumption, as mentioned in Surah An-Nahl.